TRADISI PEMBACAAN SURAT AL-WAQI’AH : Studi Living Qur’an DI PONDOK PESANTREN MAZRO’ATUL LUGHOH PARE KEDIRI - Puspitasari, Ria; Nailil Muna, Nur (LPPM IAI Hasanuddin Pare-Kediri, 2023)
This article discusses the tradition of reading Surat al-Waqi'ah which is familiarly practiced at the Mazro'atul Lughoh Islamic Boarding School. In this pesantren, all students are required to follow this routine tradition so that they are accustomed to practicing it in their daily lives. By using the study of the Living Qur'an and its approach in the form of analyzing a problem by reviewing it from the point of view of objective, expressive and documentary meanings, this paper draws the following conclusions; first, the tradition of Surah al-Waqi'ah is read regularly every day to motivate readers to get as much fadhilah as possible. Second, the objective meaning of reading the letter al-Waqi'ah, this tradition has been alive and rooted for a long time to make students become pious and pious students. Meanwhile, the expressive meaning of reading surah al-Waqi'ah can provide relief in times of trouble, ease in solving problems, and easy to obtain sustenance. The meaning of the documentary can make students become people who are disciplined in religion, especially those related to God (hablun minallah) and also with fellow human beings (hablun minannas).